Phonemic segmentation, not onset-rime segmentation, predicts early reading and spelling skills - Nation, K; Hulme, C (1997)
CHILDREN (ranging in age from 5 1/2 to 9 1/2 years) were given four tests of phonological skill. The relationships between these measures and their predictive relationship with reading and spelling ability were investigated. Performance at phonemic segmentation, rhyme sound categorisation, and alliteration sound categorisation improved with age, but all age groups performed onset-rime segmentation at a similar level. Although phonemic segmentation was an excellent predictor of reading and spelling ability, onset-rime segmentation was not. Rhyme and alliteration sound categorisation scores did account for statistically significant variance associated with reading and spelling ability, but they were poorer predictors than was phonemic segmentation. It is concluded that phonemic awareness is an important predictor of reading and spelling ability, even in the early stages of development. Our findings question the emphasis that has sometimes been placed on rhyming skills as predictors of reading and spelling ability.